The Role of Legal Audit in Collection Loan Debts through State Attorney (Study at Bambang Santoso & Partners Law Firm) - Ahmadi, Ahmadi; Nurwani, Nurwani (Jurnal Ekonomi : Journal of Economic, 2025)
This study aims to analyze the Role of Legal Audit in Debt Collection Through State Attorney (Study on Law Firm Bambang Santoso & Partners) . This study is a qualitative descriptive study with a case study approach. Data collection through interviews, observations and document studies. Based on the results of the study Legal audit or commonly called Legal audit is a legal examination and analysis of the implementation of various provisions of laws and regulations by certain parties who are the targets of legal audits, both individuals and institutions. Legal audits are intended to determine the level of compliance or violation of the company against applicable laws, including in violations of bad debts. Bad debts are conditions where debtors, both individuals and business entities, are unable to pay installments or debts they have to the lender on time. In essence, handling bad debt cases through the courts is not a simple process. In handling a fiat execution application for bad debt cases through the district court, there are several stages that must be followed.